Peran guru dalam implementasi pendidikan karakter siswa melalui trilogi kepemimpinan di kelas IV SD Negeri Tamansari 1 Yogyakarta - Sinta Mardikawati; Trisharsiswi Trisharsiwi (Universitas Sarjanawiyata Tamansiswa, 2023)
This study descriptively aims to determine the role of teachers in the implementation of student character education through Leadership Trilogy in grade IV SD Negeri Tamansari 1 Yogyakarta. The purpose of this study is to find out the supporting factors of the teacher's roles in the implementation of student character education through Leadership Trilogy in grade IV SD Negeri Tamansari 1 Yogyakarta, to discover inhibiting factors of teacher's role in the implementation of student character education through Leadership Trilogy in grade IV SD Negeri Tamansari 1 Yogyakarta, and to perceive solutions made by teachers as in the implementation of student character education through Leadership Trilogy in grade IV SD Negeri Tamansari 1 Yogyakarta. The type of this research is descriptive qualitative research. The primary data sources in this study are principals and grade IV teachers of SD Negeri Tamansari 1 Yogyakarta. The researcher uses observation, interview, and documentation as data collection techniques. This research instrument is a guideline for observation, interviews, and documentation. The steps conducted by the researcher are testing the validity of the data using triangulation of sources, techniques, time, and using reference materials. Data analysis techniques in this study utilize Miles & Huberman's analysis which consists of data collection, data reduction, data presentation, and conclusions. The results show that; (1) the role of teachers in the implementation of student character education through Leadership Trilogy is very important, because teachers as educators, guides, motivators, provide direction in case students are wrong and teachers play an important role as role models in terms of providing positive examples of refraction for students; (2) as in supporting factors, there are self-motivation, adequate school facilities, infrastructure, positive school habituation and culture, a comfortable environment, the quality of teacher competence, collaboration between school residents, parents, and the community in providing examples of positive attitudes and habituation to students; (3) inhibiting factors are the absence of positive habituation in students in the family environment, lack of support from parents, family background and poor community environment; (4) the solution made by teachers in overcoming problems in the implementation of student character education through Leadership Trilogy are that teachers provide an understanding of the importance of character education, always establish good communication and coordination with parents, provide good examples and habituation to students, become a place of consultation for students, always provide enthusiasm and motivation to students.